ANALISIS PENGARUH TIPE INDUSTRI, UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE DAN KUALITAS TATA KELOLA PERUSAHAAN TERHADAP CARBON EMISSION DISCLOSURE (Studi Empiris pada perusahaan non keuangan yang mengeluarkan sustainability report dan terdaftar di BEI tahun 2015-2017) - Fatkhi Asri Mulya; Abdul Rohman (Diponegoro Journal of Accounting, 2020)
This study aims to analyze the factors that influence carbon emission disclosure in non-financial companies that disclose sustainability reports and are listed on the Indonesia Stock Exchange in 2015 -2017. The factors tested in this study are carbon emission disclosure as the dependent variable while the industry type, company size, profitability, leverage, and quality of corporate governance as independent variablesThe sample of this study consisted of 57 companies listed on the Indonesia Stock Exchange (IDX) and revealed the sustainability report in the period 2015-2017. This study uses secondary data and in the selection of samples using a purposive sampling method. Analysis model using multiple linear regression analysis.The results of this study indicate that the variables of industry type, company size, and quality of governance have a significant effect on carbon emission disclosure. While the profitability and leverage variables have no significant effect on carbon emission disclosure.